Spatial Planning Concept for Genetic Resource of Local Paddy Development to Support Sustainable Agriculture in Central Kalimantan - Andy Bhermana; Susilawati Susilawati (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
Central Kalimantan region with an area of 15,451,287 hectares has in large number of biodiversity including genetic resources of local paddy plant. One of the threats to the preservation of genetic resources for local paddy in Central Kalimantan include the intervention of human activity through land use and conversion of forest land for plantation industries expansion. The availability of land resources with its geographic areal potential as the original habitat of genetic resouce of food crops in Central Kalimantan need to be managed rationally and sustainable through preparing spatial planning concept. The objective of study was to establish the concept of regional planning in order to determine land allocation for conservation area. Exploration survey methods was used to inventory the existence of genetic resource of local paddy plant as objects of analysis for drafting planning concept. Geographic information system (GIS) application was used to assist the process of spatial analysis in order to produce spatial information of regional planning as part of the GIS. The results of the inventory and spatial analysis explained that number of diversity of genetic resource for local paddy  in wetlands was 55 plants while in for uplands, there were 68 plants of local paddy, spatially located at river streams associated with settlement areas. The concept of regional planning for the allocation of wetland conservation area involve Kotawaringin Barat, Kotawaringin Timur, Seruyan, Pulang Pisau dan Kapuas,  with areas priority of Kotawaringin Timur and Pulang Pisau. Meanwhile, for uplands, the allocation was addressed to Lamandau, Kotawaringin Barat, Katingan, Gunung Mas, Pulang Pisau, Kapuas Barito Timur, Barito Utara dan Murung Raya with priority emphasis on Lamandau and Katingan regency.